Ten Years of Leadless Cardiac Pacing - Breeman, Karel T.N., MD, MSc; Tjong, Fleur V.Y., MD, PhD; Miller, Marc A., MD; Neuzil, Petr, MD, PhD; Dukkipati, Srinivas, MD; Knops, Reinoud E., MD, PhD; Reddy, Vivek Y., MD (Journal of the American College of Cardiology, 2024)
AbstractLeadless pacemakers (LPs) are self-contained pacemakers implanted inside the heart, providing a clinical strategy of pacing without pacemaker leads or a subcutaneous pocket. From an experimental therapy first used clinically in 2012, a decade later this technology is an established treatment option. Because of technologic advances and growing evidence, LPs are increasingly being used. Herein, the experience gained from a decade of leadless pacing is reviewed. We cover the safety and efficacy of single-chamber LPs, including comparisons with transvenous pacemakers and various models, and the initial clinical results of the first dual-chamber LP system. Furthermore, evidence and considerations regarding the optimal replacement strategy will be covered. Finally, we discuss future device developments that may broaden indications, such as LPs communicating with subcutaneous implantable cardiac defibrillators and energy-harvesting LPs.